1990
DOI: 10.1111/j.1471-4159.1990.tb08839.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Treatment of Rats with SCH‐23390 or Raclopride Does Not Affect the Concentrations of DARPP‐32 or Its mRNA in Dopamine‐Innervated Brain Regions

Abstract: DARPP-32 (dopamine- and cyclic AMP-regulated phosphoprotein, Mr = 32,000, as determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis) is a neuronal phosphoprotein that is enriched in neurons which possess dopamine D1 receptors, particularly striatonigral neurons. In rat brain slices, the phosphorylation state of DARPP-32 is regulated by dopamine, acting through the dopamine D1 receptor and the adenylyl cyclase system. This study reports that chronic blockade (21 days) of either dopamine D1 rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
14
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 15 publications
6
14
0
Order By: Relevance
“…Since it was showed that DARPP-32 is downregulated in PFC of schizophrenia subjects [10,11] and that there are genetic variations associated with PFC cognitive functions [34], we did not find alterations in the expression of DARPP-32 in five brain regions, PFC, HP, ST, CX and CB, of rats after chronic treatment with typical or atypical antipsychotics. Our results of chronic treatment with typical antipsychotic was similar to that already observed in other studies with chronic treatment with haloperidol or a specific D 2 antagonist, raclopride [35,36].…”
Section: Discussionsupporting
confidence: 93%
“…Since it was showed that DARPP-32 is downregulated in PFC of schizophrenia subjects [10,11] and that there are genetic variations associated with PFC cognitive functions [34], we did not find alterations in the expression of DARPP-32 in five brain regions, PFC, HP, ST, CX and CB, of rats after chronic treatment with typical or atypical antipsychotics. Our results of chronic treatment with typical antipsychotic was similar to that already observed in other studies with chronic treatment with haloperidol or a specific D 2 antagonist, raclopride [35,36].…”
Section: Discussionsupporting
confidence: 93%
“…BDNF also transiently increases phosphorylation of CREB in MSNs (Stroppolo et al, 2001), and it is possible that DARPP-32 induction by BDNF is in part dependent on Egr-1 induction by phosphorylated CREB. This process, however, must be context specific because other inducers of CREB phosphorylation, most notably dopamine and its agonists, do not alter expression of DARPP-32 in MSNs Grebb et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true in the case of dopamine antagonist therapy, in which side effects and drug efficacy are often manifest after long-term receptor blockade. There have been a number of studies evaluating the effects of chronic exposure to selective antagonists, however these studies have largely focused on contrasting the effects of D1 or D2 selective antagonists administered independently (Duffy et al, 1992;Vaccheri et al, 1987;Esposito and Bunney, 1989;Lublin et al, 1993;LaHoste and Marshall, 1991;Grebb et al, 1990). Only a limited number of studies have examined the chronic effects of D1 and D2 antagonists administered in combination (Schettini et al, 1992;Hess et al, 1988;, and there has been, to date, no systematic investigation of all of the potential interactions between dopamine receptor subtypes which could accompany chronic drug exposure.…”
Section: Introductionmentioning
confidence: 96%